PERAN PENGGERAK PROSES PENDIDIKAN AGAMA ISLAM (PAI) DI SMK N 3 KASIHAN BANTUL (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
Schools as institutions of formal education is a strategic place for melakukanpembinaan religious experience for students. In this guidance, can not escape the role of the main driving Islamic Religious Education (PAI) in school. This study aims to determine how the duties and functions of the driving role of the Islamic Religious Education (PAI) at SMK N 3 Kasihan Bantul. This study uses kualitatifdengan approach to data collection techniques such as observation, documentation, and interviews. The results showed that the driving role of PAI diSMK N 3 Kasihan Bantul has not been able to encourage religious activities to the fullest. Board teachers as a driver still is individualized and less attention to the school committee and the idea of the strategic thinking so that school policy has not been able to motivate the religious activities and religious practice for siswa. Coordinating function in the industrialized world in the development cooperation program has not been optimized so that the industry practice in SMK N 3 yet attention to aspects of the practice of PAI.